The Effect Of Financial Literacy And Lifestyle On Savings Interest Moderated By Gender Among State-Owned Bank Customers In Palangka Raya City - Gresia Puspitasari; Luluk Tri Harinie; Ani Mahrita; Rita Sarlawa (Utan Kayu Publishing, 2025)
This study aims to examine the effect of financial literacy and lifestyle on saving interest, with gender as a moderating variable, among customers of state-owned banks (BUMN) in Palangka Raya City. The study is motivated by the phenomenon of low saving interest despite the increasing use of banking services. This research employs a descriptive quantitative approach. Data were collected through questionnaires distributed to active customers of Bank BRI, Bank Mandiri, Bank BNI, and Bank BTN in Palangka Raya City. The collected data were analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with the assistance of SmartPLS software. The results show that financial literacy has a positive and significant effect on saving interest. Lifestyle also has a positive and significant effect on saving interest. However, gender does not moderate the relationship between financial literacy and saving interest, nor the relationship between lifestyle and saving interest. These findings indicate that financial literacy and lifestyle play an important role in encouraging saving interest among customers of state-owned banks, regardless of gender differences. This study is expected to contribute to behavioral finance literature and provide practical insights for banking institutions in designing strategies to enhance customers’ saving interest.